Оцінка впливу автозаправних станцій на навколишнє середовище - Івасенко, Віталій Михайлович; Винниченко, Тетяна Олександрівна (НТУ "ХПІ", 2017)
В даній роботі представлена методика для визначення просторового впливу автозаправних станцій на їх оточення. Метод заснований на тому факті, що відношення концентрацій ароматичних і ациклічних вуглеводнів в повітрі автозаправних станцій (в основному визначається викидами бензину з резервуарів та паливо заправних пістолетів) відрізняється від знайденого в міському повітрі (в основному визначається вихлопними газами автотранспортних засобів). Ця методика повинна допомогти створити "пояс" навколо заправних станцій, де буде обмежено вплив на населення, школи і лікарні.

In hired methodology is presented for determination of spatial influence of the filling stations on their surroundings. A method is based on circumstance that relation of concentrations of aromatic and acyclic hydrocarbons in mid air the filling stations (mainly determined by the extrass of petrol from reservoirs and fuel of filling pistols) differs from found in municipal air (mainly determined by the exhaust-gass of vehicles). On the basis of it, by a border from the filling station there is the first point influence of petrol in the distance from the station, where correlation becomes equal to the value of background in city. Application of this method, includes the multidrop measuring of concentrations at the investigated filling station and adherent territory, processing of data programmatic facilities. This methodology must help to create a "belt" round the filling stations, where influence will be restrictedly on a population, schools and hospitals.
Evaluation of petrol stations on the environment
Keywords: викиди; вуглеводні; концентрації шкідливих речовин; бензол; легкі органічні сполуки; АЗС; gas stations; concentration of pollutants